FNDC5/irisin mitigates the cardiotoxic impacts of cancer chemotherapeutics by modulating ROS-dependent and -independent mechanisms - Manish Kumar; Abhishek Singh Sengar; Anushree Lye; Pranesh Kumar; Sukhes Mukherjee; Dinesh Kumar; Priyadip Das; Suvro Chatterjee; Adele Stewart; Biswanath Maity (Redox Biology)
Cardiotoxicity remains a major limiting factor in the clinical implementation of anthracycline chemotherapy. Though the etiology of doxorubicin-dependent heart damage has yet to be fully elucidated, the ability of doxorubicin to damage DNA and trigger oxidative stress have been heavily implicated in the pathogenesis of chemotherapy-associated cardiomyopathy. Here, we demonstrate that fibronectin type III domain-containing protein 5 (FNDC5), the precursor protein for myokine irisin, is depleted in the hearts of human cancer patients or mice exposed to chemotherapeutics. In cardiomyocytes, restoration of FNDC5 expression was sufficient to mitigate reactive oxygen species (ROS) accumulation and apoptosis following doxorubicin exposure, effects dependent on the irisin encoding domain of FNDC5 as well as signaling via the putative irisin integrin receptor. Intriguingly, we identified two parallel signaling cascades impacted by FNDC5 in cardiomyocytes: the ROS-driven intrinsic mitochondrial apoptosis pathway and the ROS-independent Ataxia Telangiectasia and Rad3-Related Protein (ATR)/Checkpoint Kinase 1 (Chk1) pathway. In fact, FNDC5 forms a co-precipitable complex with Chk1 alluding to possible intracellular actions for this canonically membrane-associated protein. Whereas FNDC5 overexpression in murine heart was cardioprotective, introduction of FNDC5-targeted shRNA into the myocardium was sufficient to trigger Bax up-regulation, ATR/Chk1 activation, oxidative stress, cardiac fibrosis, loss of ventricular function, and compromised animal survival. The detrimental impact of FNDC5 depletion on heart function could be mitigated via treatment with a Chk1 inhibitor identifying Chk1 hyperactivity as a causative factor in cardiac disease. Though our data point to the potential clinical utility of FNDC5/irisin-targeted agents in the treatment of chemotherapy-induced cardiotoxicity, we also found significant down regulation in FNDC5 expression in the hearts of aged mice that attenuated the cardioprotective impacts of FNDC5 overexpression following doxorubicin exposure. Together our data underscore the importance of FNDC5/irisin in maintenance of cardiac health over the lifespan.